Clinical comparison between bilateral and unilateral mandibular condyle fractures combined with symphysis fractures – A retrospective study. Issue 1 (January 2023) - Kurobane, Tsuyoshi; Nogami, Shinnosuke; Otake, Yoshio; Suzuki, Hikari; Kajita, Tomonari; Morishima, Hiromitsu; Iwama, Ryosuke; Yamauchi, Kensuke; Takahashi, Tetsu
Abstract: Objective: Effective treatment strategies for a mandibular fracture, especially a condylar fracture, have yet to be established. The purpose of the present study was to examine characteristics and treatment management practices to compare between bilateral and unilateral condyle fractures combined with a symphysis fracture. Methods: This retrospective study included 30 patients with a mandibular condyle fracture combined with a symphysis fracture. They were divided into the unilateral and bilateral condyle fracture groups. Variables noted included fracture etiology, fracture sites, treatment methods, and functional evaluations. Results: In patients with a mandibular condyle fracture combined with a symphysis fracture, the most common cause of injury was a fall. High condyle fractures accounted for the majority of bilateral fracture cases, with low condyle fractures seen in the majority of those with a unilateral fracture. Moreover, in the bilateral fracture group, in not only patients with a low condyle fracture but also those with a high condyle fracture, ORIF was performed on at least one side, with IR used for the other side, resulting in early postoperative recovery of range of mouth opening and reduction in temporomandibular joint pain. Conclusion: The results of the present study indicated that while the causes were common, condyle fracture sites differed between cases with a bilateral and those with a unilateral condyle fracture when combined with a symphysis fracture. The findings in the present study suggest that treatment with a combination of ORIF and IR may be better for obtaining good functional recovery in the bilateral fractures pattern.